PENGEMBANGAN MATERI AJAR TEKS EKSPLANASI BERBANTUAN MEDIA ASSEMBLR EDU PADA SISWA KELAS VII UPT SMP NEGERI 2 MEDAN - Agnes Derma Yani, Anggi; Hutagalung, Trisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the process of developing explanatory text teaching materials assisted by Assemblr EDU media for seventh grade students and the feasibility of the resulting product. This research is a development research (RnD) that uses the Borg and Gall development research procedure with stages a) potential and problems, b) data collection, c) product design, d) design validation, e) design revision. Product assessment was carried out by two experts, namely material experts and media experts. Data collection techniques used included observation, interviews with Indonesian language teachers, documentation and questionnaires to determine student needs. The research instruments used were student needs questionnaires and validation questionnaires from material experts, and media experts. The results showed that the product developed from the study "Development of Explanatory Text Teaching Materials Assisted by Assemblr EDU Media for Seventh Grade Students of UPT SMP Negeri 2 Medan" was included in the "Very Feasible" category. This is based on the results of material expert validation of 90% with the "Very Feasible" category, media expert validation with a value of 94% with the "Very Feasible" category. Thus, an average score of 92% was obtained, concluding that this research product is highly suitable for use in the learning process.